Islam - Beveridge, James; Millar, David (Montreal : National Film Board of Canada, 1900)
Islam is winning new converts, particularly in North Africa. This film explores the faith of the Muslims, taking you to Mecca, birthplace of the Prophet Muhammad, and to Islam's holy of holies, Ka'aba. Following the routes of Muslim conquest from Cairo to Pakistan
Keywords: Islam -- History